Mild and Efficient Copper-Catalyzed Synthesis of Trisubstituted Pyrroles - Hsu, Ming-Hua; Kapoor, Mohit; Pradhan, Tapan Kumar; Tse, Man-Him; Chen, Hsin-Ya; Yan, Man-Jun; Cheng, Yu-Tsen; Lin, Yu-Cheng; Hsieh, Cheng-Ying; Liu, Ker-Yin; Han, Chien-Chung (Synthesis, 2021)
A sustainable and time economic approach has been developed for the synthesis of polysubstituted pyrroles using copper iodide as a catalyst. The reaction proceeded through imine formation followed by cyclization with alkyne-Cu intermediate, which was supported by control experiments studies. The newly formed substituted pyrroles were obtained in excellent yields with high regioselectivity under mild conditions.
Keywords: copper; Cu-catalyzed; pyrrole; cyclization; multicomponent